Determination of vegetation characteristics and hay yield of Taşoluk natural pasture in Aydın province Karacasu district - Haydar Can Kirazlı; Ahmet Alper Babalık (Turkish Journal of Forestry)
This research was carried out in the Taşoluk natural pasture with an average altitude of 1550 meters and an average slope of 22%, located in the Karacasu district of Aydın province, during the 2022 vegetation period. In the study, the vegetation characteristics in the natural pasture area were examined. Vegetation measurements were done by using loop and quadrat methods. As a result of the research, 147 taxa belonging to 37 families were identified in the pasture area. The families with the most taxa were Asteraceae with 17 taxa, Lamiacea with 13 taxa and Poaceae with 9 taxa, respectively. The plant-covered area value of the study area was determined as 44%. In addition, 44.79% of the botanical composition of the pasture area consists of poaceae, 31.23% of fabaceae and 23.98% of other families. The above-ground biomass amount of the pasture area was determined as 302.02 kg/da, and the below-ground biomass amount was determined as 322.80 kg/da. Grazing capacity was determined as 59.88 animal units and pasture condition was determined as medium. Research results show that there is intense grazing pressure in the natural pasture area and the pasture vegetation is damaged. This situation reveals the need to reduce grazing pressure and increase quality vegetation cover that protects the soil against erosion by improving natural pastures and applying appropriate improvement methods.